Proximate Composition, Minerals and Fatty Acid Composition of Juglans Regia L. Genotypes and Cultivars Grown in Turkey - Yerlikaya, Cemile; Yucel, Sevil; Erturk, Umran; Korukluoglu, Mihriban (INST TECNOLOGIA PARANA, 2012)
The proximate composition of eleven walnut (Juglans regia L.) genotypes (28 SK 010, 28 SK 055, 28 SK 041, 28 SK 601, 28 SK 925, 28 SK 028, 28 SK 118, 28 SK 350, 28 SK 930, 28 SK 850, 28 SK 036) and three walnut cultivars (Sebin, Bilecik, Kaman 1) produced in Turkey were determined. The oil content of the samples ranged from 61.32 to 69.35%, corresponding to an energy value of approximately 710 kcal per 100 g of kernel. The protein content ranged from 10.58 to 18.19%, and the carbohydrate composition was between 9.05 and 18.92%. The ash content ranged from 1.53 to 1.99%, and the moisture content of the kernels was between 1.91 and 4.48% the oleic acid content of the oils ranged from 17.90 to 33.35% of the total fatty acids. The linoleic acid content ranged from 43.15 to 60.20%. The linolenic acid content ranged from 9.98 to 13.00%. The palmitic acid content was between 5.21 and 8.40%. Stearic acid ranged from 2.36 to 4.25%. Potassium was the major mineral in all the samples, ranging from 359.73 to 482.97 mg/100 g. Calcium was the next most abundant mineral, ranging from 109.45 to 335.97 mg/100 g, followed by magnesium, ranging from 126.01 to 165.15 mg/100 g.
Keywords: Juglans regia L.; walnut; proximate composition; fatty acid; CHEMICAL-COMPOSITION; PERSIAN WALNUT; ZEALAND; SEEDS; Life Sciences & Biomedicine - Other Topics